Age and stage dependency of estrogen receptor expression by lymphocyte precursors - Igarashi, Hideya (The National Academy of Sciences, 2001)
Sex steroids negatively regulate B lymphopoiesis in adult mice. Paradoxically, lymphocytes arise during fetal life, when estrogen levels are high and maternal lymphopoiesis is suppressed. Here we demonstrate that embryonic B lymphopoiesis was unaffected by estrogen, but sensitive to glucocorticoids. Both fetal and adult precursors contained glucocorticoid receptor transcripts, but only adult precursors expressed estrogen receptor α and β together with the androgen receptor. Fetal hematopoietic cells did not efficiently acquire functional estrogen receptors after transplantation to irradiated adult mice. Sex steroid receptors were also expressed in a stage- and developmental age-dependent fashion in human precursors. A developmental switch in responsiveness of hematopoietic cells to sex steroids may be essential for formation of the immune system.